1971
DOI: 10.1113/jphysiol.1971.sp009435
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ethacrynic acid and other sulphydryl reagents on sodium fluxes in frog muscle

Abstract: 1. Ethacrynic acid (2 m M) increased the sodium efflux from freshly dissected frog sartorius muscles. This increase was not observed in muscles previously treated with strophanthidin. 2. In strophanthidin‐treated muscles, the addition of ethacrynic acid (2 m M) caused a reduction of sodium efflux. The value of efflux reached in these muscles is similar to that observed in muscles immersed in sodium‐free solutions containing strophanthidin. 3. Ethacrynic acid reduced sodium influx into strophanthidin‐treated mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

1972
1972
1985
1985

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…The paired muscle was exposed to progressively increasing ouabain concentrations at intervals of 1 hr until the concentration reached 1 x 10-6 M. In other experiments, we found that concentrations of ouabain as high as 10-3 M did not cause greater inhibition than 10-6 M. With all the ouabain concentrations tested, inhibition reached equilibrium about 50 min after the addition of the glycoside. In agreement with previous findings maximum concentrations of ouabain only inhibited Na efflux to 49 + 2 % the control level; most of the remaining T5X10-6M o t/I~~~~~~~~~8 efflux consists of an exchange diffusion process (Horowicz, 1965;Keynes & Steinhardt, 1968;Beaugse & Sjodin, 1968, Erlij & Leblanc, 1971). In Fig.…”
Section: Resultssupporting
confidence: 77%
“…The paired muscle was exposed to progressively increasing ouabain concentrations at intervals of 1 hr until the concentration reached 1 x 10-6 M. In other experiments, we found that concentrations of ouabain as high as 10-3 M did not cause greater inhibition than 10-6 M. With all the ouabain concentrations tested, inhibition reached equilibrium about 50 min after the addition of the glycoside. In agreement with previous findings maximum concentrations of ouabain only inhibited Na efflux to 49 + 2 % the control level; most of the remaining T5X10-6M o t/I~~~~~~~~~8 efflux consists of an exchange diffusion process (Horowicz, 1965;Keynes & Steinhardt, 1968;Beaugse & Sjodin, 1968, Erlij & Leblanc, 1971). In Fig.…”
Section: Resultssupporting
confidence: 77%
“…Since in normal Ringer the muscle fibres are close to steady state, the net Na+ flux being practically zero, one should expect that about 38 % of the Na+ ions moving inward do so via exchange diffusion. This is in good agreement with the results of Erlij & Leblanc (1971). They estimate that 33 % The stimulated Na+ influx Most determinations of the resting Na+ influx were obtained in experiments in which pairs of muscles were exposed to the radioactive solution and one of them stimulated at the end of the loading period as described in the Methods section.…”
Section: The Resting Na+ Influxsupporting
confidence: 78%
“…When 5 x 10 5M PCMBS was added to one muscle, AIB efflux was reduced to a new steady low level, while the addition of 10-3M to the paired muscle caused a transient reduction which was rapidly followed by an increased efflux. The finding that the inhibitory effects on amino acid efflux are reduced when PCMBS concentration is increased beyond a certain level, is similar to observations on the effects of PCMB on the ouabain-insensitive Na § efflux (Erlij & Leblanc, 1971). As suggested by the experiment in the inset of Fig.…”
Section: Pcmbs and Other Inhibitorssupporting
confidence: 74%